ANALYZING FOUR IDENTITY STATUS ON SAIKAKU’S SHORT STORY “TWO OLD CHERRY TREES STILL IN BLOOM” TO ENHANCE CRITICAL READINGIN - Suseno, Edy (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The short story could be the media to teach something to the readers. “Two old cherry trees still in bloom” for example, is written by Saikaku. Through his work, Saikaku would like to show the readers the implementation of 4 identity-statuses. He brought the readers into critical reading to help them find the identity. To analyze the 4 identity status content in his short story, the coding analysis was used. By analyzing, it could be seen that 4 identity-status categories comprise identity diffusion, identity foreclosure, identity moratorium, and identity achievement. Each status has two codes like uncertainty and unknown in identity diffusion, admiration and sympathy in identity foreclosure, struggle and chasing in identity moratorium, and settle and completion in identity achievement. Through the analysis, Saikaku shows the readers that to harmonize oneself as an individual and community member, someone needs to develop his curiosity through implementing identity moratorium to satisfy his lacking of background knowledge. Moreover, developing a sense of love is very essential to keep someone digging something out sufficiently through identity foreclosure to reach the ultimate goal of life.